An answer from the silence : a story from the mountains - Frisch, Max, 1911-1991 (Seagull, 2011)
This novel by esteemed Swiss writer Max Frisch is an exploration of the question: 'Why don't we live when we know we're here just this one time, just one single, unrepeatable time in this unutterably magnificent world?!' This outcry against the emptiness of ordinary, everyday life uttered by the hero of Frisch's book is countered by 'an answer from the silence' he meets when face to face with death. When An Answer from the Silence begins, the protagonist has just turned thirty and is engaged to be married and about to start work as a teacher.